Student Anxiety About Online Learning During The Covid-19 Pandemic - Nurul Anwar; Mohd Sani Ismail; Sar'in Sar'in (Jurnal Mantik, 2022)
The use of online platforms is on the rise. Coupled with the COVID-19 pandemic has changed many aspects of modern life, especially education. The existence of online learning also has psychological. Anxiety is a typical response that expresses "alertness" and prompts a person to engage in creative activities to reduce their worry about the unknown. This study aims to describe the level of anxiety and identify what causes it in students at Hamzanwadi University, Indonesia. This research is in the form of descriptive using quantitative methods. The random sampling method was used in this study. Sample The study was as many as 33 students. Collecting data using research questions forms anxiety which is formed from the theory of Sigmund Freud. When the value has multiplied the reliability of Cronbach's Alphas through pilot studies and factor analysis respectively namely 0.865. The results showed that there were 3 aspects of anxiety, namely behavioral, cognitive, and high feelings. Students feel uncomfortable following online learning so they prefer to avoid online learning methods. The implications of this study can be used by lecturers as a guide in understanding student conditions and the effectiveness of online learning.